Ensino de história : realidade aumentada enquanto recurso pedagógico - Castro, Thomas Selau de (2021)
Introduction: Education in the 21st century has brought challenges to History teachers that need to be overcome. Digital technologies, when used as pedagogical resources, can collaborate in this task. Augmented Reality (AR) is a digital technology that projects digital objects in real environments. AR may be considered a potential pedagogical resource that integrates playful, interactive, and technological elements in History teaching. Objective: We aim to identify potentialities, challenges, and limitations of using Augmented Reality as a pedagogical resource, based on perspectives and experiences of graduate students and professionals in History teaching. Methodology: We use Participatory Qualitative Research along with Action Research methods to analyze data collected from experience reports written for the extension course entitled “History Teaching: Augmented Reality as pedagogical resource”, relating them to the theoretical conceptions established. Data were collected from questionnaires applied to the participants as the course’s evaluative activities. Results: The participants demonstrated a positive attitude towards the use of Augmented Reality in their pedagogical practices, presenting different possibilities of use of this digital technology in History teaching. Conclusions: Augmented Reality is a digital technology that enhances History teaching, even though there are technical and pedagogical limitations to be faced by teachers and other users. It is pertinent to continue investigating AR’s potential as a pedagogical resource for History teaching, its impacts and students learning outcomes.